Physiological Responses during Cycle Ergometry at a Constant Perception of Effort - Cochrane, K. C.; Housh, T. J.; Bergstrom, H. C.; Jenkins, N. D. M.; Johnson, G.; Schmidt, R. J.; Cramer, J. T. (International Journal of Sports Medicine, 2015)
13 subjects performed an incremental test to exhaustion, 4, 8-min submaximal rides, and a 1-h ride at the rating of perceived exertion (RPE) that corresponded to the physical working capacity at the OMNI threshold (PWCOMNI) to examine: 1) the oxygen consumption (V̇O2), heart rate (HR), minute ventilation (+V̇E), respiratory frequency (FR), and power output responses during 1-h work bouts at a constant RPE that corresponded to the PWCOMNI; and 2) the ability of current models to explain the responses for physiological and perceptual parameters during the 1-h work bouts. The RPE that corresponded to the PWCOMNI represented a sustainable exercise intensity (56±5% (V̇O2Peak) within the moderate-intensity domain. The mean, normalized slope coefficients for the V̇O2, +V̇E, and power output vs. time relationships during the 1-h rides were significantly less than zero. The mean, normalized slope coefficient for the FR vs. time relationship during the 1-h rides, however, was not significantly different from zero. Thus, RPE most clearly tracked FR responses during the 1-h rides. It was hypothesized that afferent feedback from respiratory muscles may have mediated the perception of effort during cycle ergometry at a constant RPE in the moderate-intensity domain.
Keywords: exercise intensity; power output; feedback models; aerobic evulation; RPE